Prevalence and socio-behavioral factors associated with sugar-sweetened beverages consumption among 15 years and older persons in South Africa - Pengpid S (Dove Medical Press, 2019)
Supa Pengpid,1,2 Karl Peltzer21ASEAN Institute for Health Development, Mahidol University, Salaya, Phutthamonthon, Nakhonpathom, Thailand; 2Research and Innovation Office, North West University, Potchefstroom, South AfricaObjective: The aim of this study was to assess the frequency of sugar-sweetened beverages (SSB) consumption and its relationship with socio-behavioral factors using national population-based data in South Africa.Subjects and methods: Cross-sectional data were analyzed from the South African National Health and Nutrition Examination Survey (SANHANES-1) in 2012. The population sample included 15,179 adults (median age=34.0 years, interquartile range=25, range=15–98 years) who participated in the SANHANES-1.Results: Overall, the study participants consumed 33.9% none, 48.3% 1–3 times, 7.2% 4–6 times, and 10.6% every day soft drinks in the past week (or an equivalent of an average of 0.30 servings, SD=0.3, per day); 43.4% had consumed no sweetened fruit juice, 42.3% 1–3 times, 5.2% 4–6 times; and 9.1% daily sweetened fruit juice (or an equivalent of an average of 0.25 servings, SD=0.3, per day). The prevalence of daily SSB (soft drink and/or sweetened fruit juice) consumption was 16.0% (or an equivalent of an average of 0.54 servings, SD=0.5, per day). In the final logistic regression model, younger age, urban residence, perceived overweight, fruit consumption, fresh fruit juice consumption, and having had processed meat and fried food from street vendors were associated with SSB consumption. In addition, problem drinking and physical activity were associated with daily soft drink consumption, and higher sedentary time was associated with daily sweetened fruit juice consumption.Conclusions: The study found a high prevalence of daily SSB consumption and identified several socio-behavioral factors that can be targeted in public health intervention programs.Keywords: sugar-sweetened beverages, socio-behavioral factors, adolescents, adults, South Africa